Considering the Effectiveness of Local Democracy After the Separation of Elections: A Normative and Empirical Study of Constitutional Court Decision 135/PUU-XXII/2024 - Isnaeni, MH.; Sukamdi, Sukamdi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Abstract: The Constitutional Court Decision Number 135/PUU-XXII/2024 has significantly reshaped Indonesia’s electoral architecture by mandating the separation of national and local elections. This study aims to assess the effectiveness of local democracy following this separation, using both normative and empirical approaches. The findings suggest that while separating elections may enhance voters’ focus on local issues, it also presents challenges related to budgetary burden, continuity of implementation, and regulatory complexity. The study recommends the harmonization of electoral regulations and the strengthening of electoral human resources capacity to ensure the sustainability of quality local democracy.